Identification of Novel Locus RsCr6 Related to Clubroot Resistance in Radish (Raphanus sativus L.) - Gan, Caixia; Yan, Chenghuan; Pang, Wenxing; Cui, Lei; Fu, Pengyu; Yu, Xiaoqing; Qiu, Zhengming; Zhu, Meiyu; Piao, Zhongyun; Deng, Xiaohui (Frontiers in Plant Science, 2022)
Clubroot is one of the devastating diseases causing the substantial yield loss of radish in China. However, the inheritance of clubroot resistance and molecular mechanism in the process of clubroot infection in radish remains largely unclear. In this study, two inbred lines, a clubroot resistant radish ‘GLX’ and a clubroot susceptible radish ‘XNQ’, were employed to analyze the inheritance of the clubroot resistance in radish. This study aims to identify and fine map the novel locus of clubroot resistance gene, named RsCr6. Genetic analysis revealed that the clubroot resistance was controlled by a single dominant locus with a Mendelian ratio of 3:1. The bulked segregant analysis in combination with whole genome resequencing (BSA-seq) was applied to detect the target region of RsCr6 on chromosome Rs8. Using the method of linkage analysis, the RsCr6 locus was located between two markers HB321 and HB331 with an approximate 92 kb interval. Based on the transcriptome data in the RsCr6 locus, a differentially expressed gene R120263140 was identified as the candidate gene, and this gene encoded a MIZU-KUSSEI-like protein. Additionally, three core breeding materials containing the two reported QTLs and our newly identified locus RsCr6 targeting clubroot resistance were obtained by marker-assisted selection technology. Our discovery of RsCr6 locus lays a solid foundation for the genetic cloning, and promotes the breeding of clubroot resistance cultivar in the near future.